COMMUNICATION STRATEGIES IN THE DA‘WAH ACTIVITIES OF MAJELIS TAKLIM AL-ISTIQOMAH - Dadan Sunandar; Achmad Faisal Fikri Zamzamy (Sekolah TInggi Ilmu Dakwa dan Komunikasi Islam (STIDKIS) Al Mardliyyah Pamekasa, 2025)
This study examines the da‘wah strategies of Majelis Taklim Al-Istiqomah Klender in enhancing adolescents’ understanding of basic religious knowledge through the Tuhfatus Shibyan media in the digital era. Tuhfatus Shibyan is a nazm-based (rhymed poetry) text containing materials on Ilmu Tauhid (Islamic theology), Fiqh (Islamic jurisprudence), Sirah Nabawiyah (Prophetic biography), and maqolah / mahfudzat (aphorisms), designed to attract adolescents’ interest through an interactive and easily memorizable approach. This study employs a qualitative descriptive approach, using data collection techniques including observation, in-depth interviews, and documentation. The findings indicate that Tuhfatus Shibyan is implemented through structured teaching and Santri Basic Discipline Training (Latihan Dasar Kedisiplinan Santri, LDKS), which integrates religious education with character development. The study confirms that creative non-formal da‘wah approaches, such as Tuhfatus Shibyan, are relevant for enhancing adolescents’ basic religious understanding, with potential for adaptation into digital formats to meet the challenges of the digital era. The implications of this study recommend that Majelis Taklim organizers integrate technology into da‘wah strategies and expand collaborative networks with other communities.